Performance of Secondary Schools in Rukungiri District - Alphonse, Byamukama (Kabale University, 2023)
The study examined the performance of secondary schools in Rukungiri District. The research was carried out in the district using a cross-sectional study design that included eight secondary schools founded by the government and the church from four sub-counties: Nyakagyeme, Rukungiri municipality, Kebisoni, and Nyarushanje, with each sub-county providing two schools. The researcher discovered a number of factors related to school discipline, climate, and quality of students as having a considerable effect on students' academic performance at UCE. Lack of motivation by teachers and students, delayed fee payment and remittance of teachers' due allowances, inadequate teaching materials, limited strategies to improve academic performance by school authorities, and students' level of discipline were said to be some of the main reasons why schools performed averagely and poorly at UCE. It recommended improved welfare for teachers in order to attract and retain experienced and qualified teachers in respective schools; commitment by the schools' administration to improve academic performance at both local and national level examinations; students' involvement and participation to improve their own academic performance; and admission of students with good grades in senior one and upper level, especially candidate classes, as a way of reducing the number of failures at UCE.